Genome-Wide Analysis of Soybean Lateral Organ Boundaries Domain Gene Family Reveals the Role in Phytophthora Root and Stem Rot - Feng, Siqi; Shi, Jinxia; Hu, Yongkang; Li, Die; Guo, Liang; Zhao, Zhibo; Lee, Gang-Seob; Qiao, Yongli (Frontiers in Plant Science, 2022)
The plant-specific LATERAL ORGAN BOUNDARIES (LOB)-domain (LBD) proteins, a family of transcription factors, play important roles in plant growth and development, as well as in responses to various stresses. However, little is known about the functions of LBD genes in soybean (Glycine max). In this study, we investigated the evolution and classification of LBD family in soybean by a phylogenetic tree of LBD gene family from 16 species. Phylogenetic analysis categorized these proteins into two classes (Class Ⅰ and Class Ⅱ) with seven subgroups. Moreover, we found that all the 18 LBD ancestors in angiosperm were kept in soybean and common bean genomes and genome-wide duplication, suggesting the main force for the expansion of LBD from common bean to soybean. Analysis of gene expression profiling data indicated that 16 GmLBD genes were significantly induced at different time points after inoculation of soybean plants (cv Huachun 6) with Phytophthora sojae (P. sojae). We further assessed the role of four highly upregulated genes, GmLBD9, GmLBD16, GmLBD23 and GmLBD88, in plant defense in soybean hairy roots using the transient overexpression and knockdown assays. The results showed that GmLBD9 and GmLBD23 negatively regulate plant immunity against P. sojae, whereas GmLBD16 and GmLBD88 positively manipulate plant immunity against P. sojae. Collectively, our findings expand our knowledge of the origin and evolution of GmLBD gene family in soybean and promote the potential application of these genes in soybean genetic improvement.